Quality of Life and Dance in Middle Aged and Older Adults: A Literature Review - Bougiesi Μαρία; Gianni Αικατερίνη; Zisi Βασιλική (Inquiries in Physical Education and Sport, 2014)
Quality of life is what most, if not all, people seek and pursue. However, as the quality of life has a different meaning for each individual, there are different approaches on the definition of quality of life. The quality of life - exercise relationship is a research direction with increasingly growing interest. Recently, the above relationship has been studied using dance as a suitable form of exercise for all ages which in many cases seems to be beneficial for both physical and mental health. Greek dance seems to have a positive effect on the quality of life of both healthy and unhealthy people, improving characteristics of mental health and sometimes it seems to be more efficient on this compared to other types of exercise. This research evidence are linking dance with higher quality of life and lead to research questions about the type and the dose response of dance based interventions.